Measuring the Teacher's Sense of Efficacy Scale for Teachers of Children with Special Needs in Indonesia - Rachmahana, Ratna Syifa'a; Chirzin, Muhammad; Bashori, Khoiruddin; Purnomo, Halim (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2025)
The aim of this research is to test the validation and analysis of the Teacher's Sense of Efficacy Scale (short form) measurement tool for teachers of children with special needs in Indonesia . In this study, researchers tested three dimensions developed by Tschannen-Moran and Hoy (2001) for measuring teaching efficacy , namely Efficacy in Classroom Management, Efficacy in Student Engagement, and Efficacy in Instructional Strategies with a total of 12 items. The research subjects were 301 teachers of children with special needs . The data analysis method used in this research is confirmatory factor analysis (CFA) with the help of JASP software 0.1 8. 3. Based on the analysis results obtained a GFI value of 0.9 97; CFI 0.930; TLI 0.907; RNI 0.930; SRMR 0.044; and RMSEA 0.082. This means Teacher's Sense of Efficacy Scale has an appropriate model or goodness of fit and is suitable for use in research models